Agile Processes Are the Factor of Competitive Advantage of Organizations - Rezapour Nasrabad, Rafat; ., . (International Journal of Engineering and Technology, 2018)
One of the important and basic reasons of using technology and relevant tools is creating speed and agility in the processes and current activities of organization with correct and exact management of affairs and higher productivity. By suitable tools, we can predict and meet the demands and a positive cycle of creating production and service (even before fulfillment of market needs) is established and this leads to the success in competition. In an agile process, all people, institutes and organizational processes as integrated by using an advanced technology interact effectively to fulfill the needs of customers. Indeed, agility means the ability and speed of action of an organization for rapid and simultaneous application and interaction of technology, employees and management via creating rapid communicative infrastructures in purposeful, efficient and planning accountability and continuous and unpredicted changes in the needs of customers and market environmental conditions with the timely detection of opportunities. In an agile process, technology, management and personnel of organization as purposeful and planned interact in a dynamic environment in terms of unpredicted changes for rapid response to these changes. In this mini review study, after  review of the existing studies and electronic search in the local and international resources regarding the organizational agility, the researcher could explain the  structure of agile or process oriented organizations.